(untitled) (Quinto Sol, 2011)
Our purpose in this work is to show how, within the frame of the process of consolidation of the nationality initiated by the end of 19th century, Mar del Plata’s authorities found in the patriotic events a crevice, to consolidate their power and to define a history and an identity for the new city. We show that they used diverse resources to solemnize the patriotic events, but prioritized to meet the needs and urgencies of the commune. This fact was not seen as carelessness towards its patriotic task, but as an opportunity to legitimize their authority. The conformation of the political power was connected to the construction of a unifying frame of the identity. We look deeply into the character and the historicity of the problem with a parallel analysis of the commemoration of two “Centenaries” developed in the decade of 1910, one of the national order –the commemoration of the “1810 Revolution”– and the other of local order, the birth of the founder of the city in 1814.